International Seminar on Nuclear War and Planetary Emergencies, 23rd session medicine & biotechnologies, proliferation & weapons of mass destruction, climatology & El Nino, desertification, defence against cosmic objects, water & pollution, food, energy, limits of development, the role of permanent monitoring panels : "E. Majorana" Centre for Scientific Culture, Erice, Italy, 19-24 August 1998 (Science and culture series. Nuclear strategy and peace technology, 1999)
"In the opening session the Chairman of the Seminar underlined the important role of the permanent monitoring panels with respect to the 15 planetary emergencies. A special session of the Seminar was devoted to reporting on the activity of these panels. Short papers, abstracts and transparencies in the opening session introduced the subjects of the contributions: "Climatology and El Nino" (Nadia Pinardi, Neville Nicholls, Congbin Fu, Akimasa Sumi, William Sprigg and Llowell Wood) and "Desertification" (Douglas Johnson, Xinmin Liu, Lennart Olsson and Norman Rosenberg). Contributions on "Medicine & Biotechnologies" were presented by Paul Brown, Robert Will, Benardino Ghetti and Guy de The. The Theme "Defence Against Cosmic Objects" was covered by Walter Huebner, John Remo and William Bottke; "Water and Pollution" by Herman Bouwer, Gennady Palshin, David Rice and Paolo Ricci; and problems centered upon "Food" by Carlo Lerici and Silvia Franceschi, "Proliferation and Weapons of Mass Destruction" was discussed by Henning Wegener, Andrei Piontkovski, Reiner Huber, Tony Mason, Willis Stanley, Gregory Canavan and Povl Olgaard; "Limits of Development" by Hilmar Schubert and Leonardas Kairiukstis; and "Energy" by Stanislav Subbotin, Andrei Gagarinski and Eugeni Velikhov. T D Lee closed the Seminar by emphasizing the link between basic science and planetary emergencies."--Publisher's website